ALL-UKRAINIAN SCIENTIFIC AND PRACTICAL CONFERENCE “THE ROLE AND PLACE OF THE NATIONAL SPECIAL SERVICES IN THE HISTORY OF UKRAINIAN STATE BUILDING” - Колегія, Редакційна (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
On 17 March 2017, Taras Shevchenko National University of Kyiv hosted the All-Ukrainian Scientific and Practical Conference “The Role and Place of the National Security Service in the History of Ukrainian State-Building,” co-organized by Ukraine’s Security Service (SBU) and Taras Shevchenko University. Key participants included senior officials (the Prosecutor General, SBU leadership, Presidential Administration deputies, and NATO liaison), leading scholars, and practitioners. Major themes addressed: Democratic civilian oversight of intelligence services. Legal regulation of state secrecy protection and automated court document systems. SBU reform in the context of Euro-Atlantic integration, drawing on NATO experience. Functional-structural changes and new directions for counterintelligence. The conference continued in two sections—for senior experts and for early-career researchers—and its proceedings have been published online: http://science.univ.kiev.ua/sbu.pdf

17 березня 2017 року в Київському національному університеті імені Тараса Шевченка відбулася Всеукраїнська науково-практична конференція «Роль і місце національної спецслужби в історії українського державотворення», організована Службою безпеки України та КНУ ім. Т. Шевченка. У пленарному засіданні взяли участь вищі посадовці (Генеральний прокурор, керівництво СБУ, Адміністрації Президента, НАТО), провідні вчені та практики, які обговорили: Демократичний цивільний контроль за спецслужбами. Законодавче врегулювання охорони держтаємниці та автоматизованих систем документообігу. Реформування СБУ в умовах євроатлантичної інтеграції, з урахуванням досвіду НАТО. Функціонально-структурні зміни та нові напрями діяльності контррозвідки. Конференція продовжила роботу в двох секціях – для досвідчених фахівців та молодих учених – й увійшла до збірки матеріалів, доступної за посиланням: http://science.univ.kiev.ua/sbu.pdf
ВСЕУКРАЇНСЬКА НАУКОВО-ПРАКТИЧНА КОНФЕРЕНЦІЯ «РОЛЬ І МІСЦЕ НАЦІОНАЛЬНОЇ СПЕЦСЛУЖБИ В ІСТОРІЇ УКРАЇНСЬКОГО ДЕРЖАВОТВОРЕННЯ»